Faktor-Faktor Penentu Volatilitas Harga Saham Syariah Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Samsiar Samsiar; Slamet Haryono (Program Studi Manajemen FEBM UMRAH, 2023)
The purpose of this research was to determine the determinants of Islamic stock price volatility with firm size as a moderating variable. The type of this research is quantitative research using Moderate Multivariate Analysis (MRA). Data processing using E-views 9 applications.The population in this study are companies which listed on the Indonesia Stock Exchange (IDX) 2017-2021. The purposive sampling technique was used, namely there were 20 companies listed on the IDX as samples. The results of this research indicate that the Dividend Payout Ratio (DPR), Asset Growth (PAT) has no effect on stock price volatility. Meanwhile, the variable Trading Volume (VP) has a positive effect on stock price volatility. In addition, the Company (Firm Size) is unable to moderate the Dividend Payout Ratio (DPR) and Asset Growth (PAT) on Stock Price Volatility and is able to moderate Trading Volume (VP) on Stock Price Volatility.